A NEW GENUS AND SPECIES OF PISAURIDAE (ARANEAE) IN CRETACEOUS BURMESE AMBER - Penney D. (My University, 2004)
The oldest pisaurid spider Palaeohygropoda myanmarensis gen. et sp. nov. (Araneae: Pisauridae) is described from 100-107 Mya (Albian) Cretaceous amber (Burmite) from Myanmar (Burma). This specimen extends the known range of the family by approximately 60 My from the previously oldest record in Baltic amber. It predicts the presence of the extant spider families Zorocratidae, Tengellidae, Amaurobiidae and Nicodamidae at the same point in time and extends the ghost lineages of the remaining lycosoids, the stiphidioids, titanoecoids and Dionycha to the same point, thus providing further evidence that spiders were not severely affected by the end-Cretaceous mass extinction event. The new species provides evidence for freshwater habitats in the Cretaceous amber forest and is also the oldest record of a spider specialised for locomotion across the water surface film. The extant genus Hygropoda, to which the new genus is closely related, needs taxonomic revision.
Keywords: SPIDER; FOSSIL; ALBIAN; PALAEOHYGROPODA; HYGROPODA; MYANMAR; BURMA; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский